Lithogeochemistry of the sedimentary stratigraphy and metosomatic alteration in the Musselwhite gold deposit, North Caribou Lake belt, Superior province, Canada : implications for deposition and mineralization - Moran, Patrick Cowen (My University, 2008)
The Musselwhite gold deposit, 100% owned and operated by Goldcorp Inc., has cumulatively produced in excess of 2 million ounces since opening in 1997 and has a projected mine life through 2013. It is situated in the North Caribou Lake metavolcanic/metasedimentary belt in the central northwestern portion of Superior Province, approximately 430 km northwest of Thunder Bay, Ontario, Canada. The belt occurs along the contact between the North Caribou Terrane and the Island Lake Domain, with a large, crustal-scale deformation zone forming its eastern margin. The Musselwhite gold deposit is hosted by amphibolite facies metamorphic rocks dominated by banded iron formation (BIF). This study primarily focuses on the Northern Iron Formation (NIF) metasedimentary assemblage, host to the majority of gold mineralization at Musselwhite ....
Keywords: Geochemistry; Petrology; Northwestern Ontario; Musselwhite Mine; Gold ores